Proceedings of the 30th European Safety and Reliability Conference and 15th Probabilistic Safety Assessment and Management Conf 2020
DOI: 10.3850/978-981-14-8593-0_5862-cd
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Evolutionary Algorithm for the Identification of Rare Functional Dependencies in Complex Technical Infrastructures

Abstract: A Multi-Objective Evolutionary Algorithm (MOEA) is proposed for the identification of association rules describing functional dependencies in Complex Technical Infrastructures (CTIs). The algorithm uses novelty search to explore the solution space. It has been applied to a real large-scale database of alarms collected in the CTI of CERN (European Organization for Nuclear Research). The obtained results show its effectiveness in identifying rare functional dependencies not found using standard algorithms of Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The present work extends the MOEA proposed in Antonello et al (2020b) to address the above-mentioned issues. To this aim, the recently proposed metric of dependency (Antonello et al 2021c), which has been shown to discriminate rules with spurious alarms from rules describing actual FDEPs (Antonello et al 2021c), is used as fitness function within the MOEA search.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…The present work extends the MOEA proposed in Antonello et al (2020b) to address the above-mentioned issues. To this aim, the recently proposed metric of dependency (Antonello et al 2021c), which has been shown to discriminate rules with spurious alarms from rules describing actual FDEPs (Antonello et al 2021c), is used as fitness function within the MOEA search.…”
mentioning
confidence: 87%
“…When one-bit genes are employed, the initialization of the population using sub-optimal chromosomes characterized by a limited number of one-bit genes equal to 1 can facilitate the GA convergence, as shown in the context of features selection problems (Baraldi et al 2016) and association rules identification (Del Jesus et al 2011;Antonello et al 2020b). In this work, the initial population of chromosomes is created considering all the possible patterns, X ′ , made of 2 alarms ( |X � | = 2 ) which verify Eq.…”
Section: Moea Algorithmmentioning
confidence: 99%
See 2 more Smart Citations